Projecting a Future Present: Greta Thunberg’s use of Presence at the United Nations Climate Action Summit 2019 - Jelte Olthof (Res Rhetorica, 2021)
Rhetoricians have long realized that crises are, in part, the product of audience perception and therefore rhetorical choice. In this article I will demonstrate that the speech that Swedish climate activist Greta Thunberg gave at the 2019 United Nations Climate Action Summit employs presence to not only transcend her own person, but time itself, and presents climate catastrophe as a future present that should be avoided at all cost.